Representing Gender in an Indonesian EFL Textbook: Students’ Perspectives and Textbook Analysis - Hanum Salsabila; Fikri Asih Wigati; Dedeh Kartini (PROJECT (Professional Journal of English Education), 2026)
This study aimed to analyze gender representation in the textbook Bahasa Inggris: Work in Progress and to explore students’ perceptions of gender stereotypes portrayed in the textbook. This study employed a qualitative descriptive design. The data were collected through content analysis and an open-ended questionnaire distributed to 44 tenth-grade students at a senior high school in Karawang. The analysis focused on seven indicators of gender representation, namely pictures, activities, traits, role models, characters, gender mentions, and the order of name mention. The results showed that the textbook was not fully gender-balanced and still reflected gender bias in several aspects. Male characters were more dominant in most indicators, while female characters appeared slightly more frequently only in the gender mentions indicator. In addition, most students were aware of the unequal gender representation portrayed in the textbook, although several students demonstrated critical awareness toward gender stereotypes. Overall, the textbook still reflected unequal gender representation despite several positive portrayals of female characters.